Powtoon Animated Video For Teaching Tamil Grammar Skills To Students In Malaysian Secondary Schools: A Literature Review - Veerasamy, Sheela Devi; Ramasamy, Dr. Mohana Dass (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2023)
Tamil Language is an elective subject under the Pupil’s Own Language offered to students in Malaysian public secondary schools. The importance of learning Tamil language and the need to master ilakkanam to master the language was explained along with the current teaching and learning scenario in Malaysian secondary school. The purpose of this literature review paper is to provide a deeper understanding to the reason why teachers need to explore and develop resources for teaching and learning Tamil grammar skills. At the same time, the potentials of Powtoon animated video are discussed to motivate teachers to be creative and innovative to develop instructional module for teaching Tamil grammar skills at the secondary school level. This paper provided some of the identified research gaps from the literature which support the need for developing more teaching and learning resources for Tamil language instruction.